Edutainment class with foster schools - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
In conjunction with the University Social Responsibility Programme (USR) and Knowledge Transfer Programme (KTP), Akademi Pengajian Bahasa (APB) organised engaging edutainment activities at Sekolah Kebangsaan Seafield 3 and Sekolah Kebangsaan Kampung Jawa 2. The online programme took place in August 2022 and required students from this adopt-a-school initiative to participate in a Choral Speaking class and a Poetry class. The Choral Speaking class was conducted by Pavithran Ravinthra Nath, Rasyiqah Batrisya Zolkapli, Sri Fitriaty Mohd Kenali and Nadiah Hanim Abdul Wahab while the Poetry class was handled by Juliana Damsik, Nurul Nadia Samud, Norita Harijaman, and Dr Mohamad Nik Mat Pelet.